2017
DOI: 10.4103/1793-5482.144177
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous extradural and subgaleal hematoma: A rare neurosurgical crisis of sickle cell disease

Abstract: Extradural hematoma (EDH) in absence of trauma is a rare entity with only few cases reported in literature. The various causes reported include: Vascular malformation of dura, coagulopathies, sinus infection, middle ear or orbital infection, and tumor. Occurrence of spontaneous EDH as a complication of sickle cell disease is even much rarer. We report a case with sickle cell disease who presented with spontaneous extradural and subgaleal hematomas following an episode of vaso-oclusive crisis. He was managed su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…Silent and acute parenchymal infarctions and moyamoya vasculopathy comprise most neurological complications of SCD [ 1 ]. Two-third of the central nervous system complications are ischemic; intracerebral hemorrhages are less common [ 2 ]. Subarachnoid or spontaneous extradural hematomas are even less common than the other two complications [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Silent and acute parenchymal infarctions and moyamoya vasculopathy comprise most neurological complications of SCD [ 1 ]. Two-third of the central nervous system complications are ischemic; intracerebral hemorrhages are less common [ 2 ]. Subarachnoid or spontaneous extradural hematomas are even less common than the other two complications [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two-third of the central nervous system complications are ischemic; intracerebral hemorrhages are less common [ 2 ]. Subarachnoid or spontaneous extradural hematomas are even less common than the other two complications [ 2 ]. These central nervous system (CNS) complications can reach up to 6.9% in children with SCD compared to 0.5% in healthy children [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sub-galeal hematomas are more associated with epidural hematomas with underlying bone infarction. Mishra et al [ 9 ] analyzed prior published reports and found skull bone infarction in seven out of nine cases reviewed. From the reviewed case reports in adults, the mean age at presentation was found to be 19 years, which is comparable to our patient’s reported age of 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the previous reports identify skull bone infarction in the same area as the extradural hematoma and the commonest interpretation is that extradural hematomas are a complication of bone infarction disrupting the cortical bone, causing periosteal elevation and subsequent bleeding into the extradural space. There could also be a spontaneous rupture of epidural vessels in the vicinity of the infarcted bone [5][6][7][8][9].…”
Section: Skull Infarctionmentioning
confidence: 99%